Study on the Impact of Climate Change on Damage to National Roads in the Lapuko – South Konawe District/ Kendari City Boundary - Sutrisno, Muhammad; Lakawa, Irwan; Haryono, Haryono; Syamsuddin, Syamsuddin (Sultra Civil Engineering Journal (SCiEJ), 2022)
The land transportation sector is one sector that is very influential on climate change. One of the impacts faced by the road network due to climate change is damage to roadside sections. This is the basis for the researchers to conduct research in Lapuko - Boundary of South Konawe Regency / Kendari City The purpose of this study was to determine how much influence climate change, namely rainfall, humidity, and temperature had on road damage on the Lapuko - South Konawe District boundary / Kendari City. To find out how much influence the independent variable has on the dependent variable or whether there is an influence of the independent variable on the dependent variable, classical statistical analysis tests, t and F tests and the coefficient of determination test are carried out through SPSS version 24 for windows. The results of the analysis of climatic conditions on the Lapuko - Konawe Selatan Regency / Kendari City boundary with an average rainfall of 184 with the highest rainfall occurring in May while the average humidity is 92.9% and the temperature is 36.20 C which occurs from 2017 to 2021. The road conditions on the Lapuko – Konawe Selatan Regency/Kendari City boundary tend to be flexible with an average road condition level of 45.65%, moderate 43.74 and slightly damaged 8.48 and heavily damaged 2.10 from 2017 to 2021. There is the influence of climate change to road damage in the Lapuko – South Konawe District/Kendari City Boundary section with a value of 74.5%.